El Telégrafo: orígenes de un diario guayaquileño - Tamayo Cruz, Natalia Yolanda (2023)
This work was carried out within the framework of the Research Project sponsored by the University of the Arts, The Library of the Arts, history of a process attached to the Art and Social Memory Working Group. It investigates the history of Diario El Telégrafo from its foundation in 1884 to 1925 in line with the social, political and economic relations that influenced it to become the reference medium in Guayaquil. The research takes as a methodological approach the considerations raised by the history of the present time regarding the analysis of the press and relates the life stories of its first owners in order to demonstrate the social, economic and political connections that contribute to the development of the newspaper company. The story presented talks about the life of the newspaper and its founders. He hopes to develop the complex relations of the press with the economic, financial and financial power of the country and to contribute with new elements that allow rewriting the history of the written press in the country, as institutions that intervene as political actors or operators to achieve social decisions that benefit.